2007
DOI: 10.1021/jp073017d
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Characteristics of Pentaoxyethylene Decyl C10E5 and Hexaoxyethylene Tetradecyl C14E6 Ether Micelles with Uptake of n-Octanol

Abstract: Wormlike micelles of the surfactant pentaoxyethylene decyl C10E5 and hexaoxyethylene tetradecyl C14E6 ethers were characterized by static (SLS) and dynamic light scattering (DLS) experiments to examine effects of uptake of n-octanol on the micellar characteristics. The SLS results have been successfully analyzed by the light scattering theory for micelle solutions to yield the molar mass Mw(c) as a function of concentration c along with the cross-sectional diameter d of the micelle. The apparent hydrodynamic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 26 publications
2
17
1
Order By: Relevance
“…A series of the data points for the latter near w d ¼ 0:028 are the results by Hellweg and von Klitzing. 67 We find that at small w d , the cloud point curve shift to lower temperatures with increasing w d and then shift to higher temperatures at larger w d in contrast to the case of the micelle solutions containing n-alcohol [31][32][33][34][35] for which the phase boundaries monotonically shift to lower temperatures as the alcohol content increases. In panel a of Figure 25, the emulsification failure boundary schematically shown by the surface enclosed by dashed and dotted lines indicates that too much n-dodecane can not be included in the C 12 E 5 micelles at any T and w d .…”
Section: Effects Of the Uptake Of N-alcohol And N-alkanementioning
confidence: 65%
See 3 more Smart Citations
“…A series of the data points for the latter near w d ¼ 0:028 are the results by Hellweg and von Klitzing. 67 We find that at small w d , the cloud point curve shift to lower temperatures with increasing w d and then shift to higher temperatures at larger w d in contrast to the case of the micelle solutions containing n-alcohol [31][32][33][34][35] for which the phase boundaries monotonically shift to lower temperatures as the alcohol content increases. In panel a of Figure 25, the emulsification failure boundary schematically shown by the surface enclosed by dashed and dotted lines indicates that too much n-dodecane can not be included in the C 12 E 5 micelles at any T and w d .…”
Section: Effects Of the Uptake Of N-alcohol And N-alkanementioning
confidence: 65%
“…They have shown that the apparent molar mass M app of the wormlike micelles formed in the L 1 phase increases with c in the range of small c, passing through a maximum, and then decreases with increasing c at higher c. Here, M app includes two contributions, i.e., concentration-dependent molar mass M w ðcÞ of the micelles and concentration dependent structure factor Sðc; q ¼ 0Þ (q the magnitude of scattering vector) which reflects thermodynamic interactions among micelles. We have also investigated solution properties of the wormlike micelles of various C i E j containing n-dodecanol, -octanol, and n-dodecane, [32][33][34][35][36][37] by applying the same technique as in the case of the micelles of C i E j and their mixtures described above.…”
Section: Effects Of the Uptake Of N-alcohol And N-alkanementioning
confidence: 99%
See 2 more Smart Citations
“…In this series of work on micelle solutions of nonionic surfactant polyoxyethylene alkyl ethers H(CH 2 ) i (OCH 2 CH 2 ) j -OH (abbreviated C i E j ), we have characterized the wormlike C i E j micelles with various i and j containing n-alcohols, ndodecanol or n-octanol, [1][2][3][4][5] and n-dodecane 6 by static (SLS) and dynamic light scattering (DLS) measurements in order to explore effects of uptake of n-alcohol or n-dodecane into the micelles on the micellar characteristics. It has been demonstrated that the SLS results (the excess Rayleigh ratio) as a function of surfactant concentration c are successfully analyzed by a molecular thermodynamic theory 7,8 formulated with the wormlike spherocylinder model to provide us with molar mass M w ðcÞ of the micelle at a specified c along with the crosssectional diameter d of the spherocylinder, as in the case of the micelle solutions of pure C i E j and binary C i E j mixtures.…”
mentioning
confidence: 99%